Pengembangan Lembar Kerja Siswa (LKS) Berbasis Model Pembelajaran Inkuiri Terbimbing Pada Materi Termokimia - Ani Sutiani; Fayaddah Fayaddah (Universitas Negeri Medan, 2021)
This study aims to determine the feasibility of the worksheets student based on the BSNP criteria and to find out the responses of students to the designed worksheets. The method in this research uses the method of Research and Development (R&D) according to the Borg and Gall stages. The research subjects were worksheets based on guided inquiry learning models. The object of research is the thermochemical material. The results showed that the worksheets student that had been compiled had met the eligibility criteria according to the BSNP standards based on the content feasibility aspect, the presentation feasibility aspect, and the language feasibility aspect, which was obtained an average percentage of 88.55% with valid / feasible criteria and based on the feasibility aspect of graphic -the average percentage of 87.41% with valid / feasible criteria. As for the results of student responses to the designed worksheets is very high with an average percentage of 88.60%.